(untitled) (World Economics and Finance Bulletin, 2024)
The study aimed to identify the impact of the International Financial Reporting Standards (IFRS) on the quality of profits in a sample of banks listed on the Iraq Stock Exchange. The study dealt with the method of analyzing the information content of the annual financial statements published on the Iraq Stock Exchange website, which number (46) banks. (15) banks were chosen as a sample for the study for the period (2012- 2022). This sample was determined according to two basic conditions: the availability of financial statements for the year 2021 and the banks’ continuation of disclosing their data for the specified years without interruption. The independent variable was measured by international financial reporting standards ( IFRS) with a value of (1.0), and the second variable (quality of earnings) was measured with the model (Kothari et al., 2005), which is the quality of benefits. Data analysis was also conducted through the use of statistical methods and tools and the statistical program (stata), and the study concluded there is a positive moral relationship between the adoption of international financial reporting standards and the quality of profits. This means that the greater the trend towards adopting international financial reporting standards is accompanied by an increase in the levels of quality of profits. The study recommended obliging banks listed on the Iraqi Stock Exchange to implement international financial reporting standards. When preparing financial statements for the purpose of providing useful accounting information to the users of those lists, we also work to increase the awareness of investors and company managements about the importance of applying standards that will improve the quality of profits, through workshops, training courses, and scientific seminars